Relationship between Deep Marginal Elevation and Periodontal Parameters: A Systematic Review - Mohammed Fareed Felemban; Osama Khattak; Thani Alsharari; Abdulrahman H. Alzahrani; Kiran Kumar Ganji; Azhar Iqbal (Medicina, 2023)
Background and Objectives: This review focuses on reviewing studies from the literature regarding the effects of deep margin elevation on the surrounding periodontium. Materials and Methods: A review of the literature was carried out using the following online databases: Embase, The Cochrane Library, MEDLINE-PubMed and Google Scholar. Our search was limited to articles from 2010 to 2023. The search terms consisted of keywords and MeSH terms, which were ‘deep margin elevation’, ‘coronal margin relocation’, ‘periodontium’ and ‘periodontal tissues’. The literature was searched thoroughly by two reviewers. Initially, the titles of the articles were extracted. After removing irrelevant and duplicate articles, abstracts were assessed for relevant articles. Finally, the reviewers analyzed full-text articles. Results: A total of twelve articles, including one randomized clinical trial, three systematic reviews, two prospective cohort, three case series, one a clinical study, one pilot study and one a retrospective study, were selected and analyzed. Conclusions: The review suggests potential benefits of Deep Margin Elevation (DME) over surgical crown lengthening due to reduced invasiveness, yet conclusive effects on periodontal tissue remain unclear, warranting further studies on clinical parameters and inflammatory biomarkers.